Mortalidade de vespas sociais associadas ao cultivo do feijão de corda, Vigna unguiculata (L.) Walp. por agrotóxicos: diretrizes de boas práticas de manejo para a conservação da biodiversidade de insetos úteis em agroecossistemas - Assmar, Cezar Chamusca (2010)
Brazil is a country with a large agricultural vocation and this is demonstrated once it is globally recognized as the most important producer of grains, seeds, vegetable and fruit variety. The exponential population growth in the world leads to the production of more and more elaborated technologies of intervention on the management of pests, seeking a more balanced and ecologically sustainable agriculture. Aiming the contribution to the knowledge on the effect of harmful agricultural practices to the predatory social wasps populations associated to the cultivation of the cow-pea, Vigna unguiculata at the semi-arid region of Bahia, Brazil, an evaluation of the effect of insecticides on the most abundant species of social wasps was made at the locations of Besouro and Universidade Estadual de Feira de Santana – UEFS Campus (Polybia sericea, Polybia paulista, Polistes canadensis, e Polybia occidentalis). A diagnosis of the management used by small scale farmers at the area of Besouro was also made. For the laboratory phase, insecticides belonging to the main subgroups used were chosen, Lufenuron, Acefate, Carbosulfan, Cialotrin and Nim Oil (Azadiractin). This bioassay was made using a completely casual design, with 6 treatments (5 insecticides and 1 testimony) and 4 repetitions for each treatment, being each repetition formed by a group of 5 wasps. Under laboratory controlled conditions, leafs of Vigna unguiculata, treated with insecticides, were placed together with the insects confined in plastic containers (13,5 cm x 15,5 cm) and the data concerning the number of deaths was collected until the sixth hour. At the end of 24 hours from the beginning of the experiment, a final evaluation was made and the results obtained were submitted to a non-parametric analysis of variance Kruskal-Wallis on a level of 5% of probability, while to compare each wasp with the testimony a Mann-Whitney test was used, also on a level of 5% of probability. The fact that the Vigna unguiculata was cultivated in association with other cultures and the presence of fruits plants, herbs, and native species were considered important to the biodiversity of beneficial organisms such as pollinators, predators and parasites of the area, witch reflects the inexpressive utilization of insecticides by the farmers. Of the insecticides tested, at the doses recommended by the industries, azadiractin presented a significant difference in relation to the testimony, when the species tested were Polybia sericea and Polybia paulista, and cialotrin presented toxicity only for Polybia sericea. The comparison of the toxicity of the insecticides made between the wasps species demonstrated that only lufenuron presented a toxicity significantly superior, when the specie involved was Polybia sericea. In order to avoid possible alterations on the populations of Polybia sericea, one of the most abundant predators between the social wasps at the region of Feira de Santana-Bahia, we do not recommend the utilization of azadiractin (nim oil) and cialotrin to combat the agricultural pests of the region.